Characterization of mutants of Caulobacter crescentus defective in surface attachment of the paracrystalline surface layer. - Walker, S G (1994)
Strains of Caulobacter crescentus express a paracrystalline surface layer (S-layer) consisting of the protein RsaA. Mutants of C. crescentus NA1000 and CB2, isolated for their ability to grow in the absence of calcium ions, uniformly no longer had the S-layer attached to the cell surface. However, RsaA was still produced, and when colonies grown on calcium-sufficient medium were examined, large two-dimensional arrays of S-layer were found intermixed with the cells. Such arrays were not found in calcium-deficient medium even when high levels of magnesium ions were provided. The arrays could be disrupted with divalent ion chelators and more readily with the calcium-selective ethylene glycol-bis (beta-aminoethyl ether)N,N,N',N'-tetraacetic acid (EGTA). Thus, the outer membrane surface was not needed as a template for self-assembly, but calcium likely was. The cell surface and S-layer gene of assembly-defective mutants of NA1000 were examined to determine the basis of the S-layer surface attachment defect. Mutants had no detectable alteration in the rough lipopolysaccharide (LPS) or a characterized capsular polysaccharide, but another polysaccharide molecule was greatly reduced or absent in all calcium-independent mutants. The molecule was shown to be a smooth LPS with a core sugar and fatty acid complement identical to those of the rough LPS and an O polysaccharide of homogeneous length, tentatively considered to be composed of 4,6-dideoxy-4-amino hexose, 3,6-dideoxy-3-amino hexose, and glycerol in equal proportions. This molecule (termed SLPS) was detectable by surface labeling with a specific antiserum only when the S-layer was not present. The rsaA genes from three calcium-independent mutants were cloned and expressed in an S-layer-negative, SLPS-positive strain. A normal S-layer was produced, ruling out defects in rsaA in these cases. It is proposed that SLPS is required for S-layer surface attachment, possibly via calcium bridging. The data support the possibility that calcium binding is required to prevent an otherwise lethal effect of SLPS. If true, mutations that eliminate the O polysaccharide of SLPS eliminate the lethal effects of calcium-deprived SLPS, at the expense of S-layer attachment.